STRUKTUR DAN MAKNA PROSESI PERKAWINAN ADAT DAYAK NGAJU (THE STRUCTURE AND MEANING OF THE DAYAK NGAJU TRADITIONAL MARRIAGE PROCESSES) - Lastaria Lastaria; Ahmad Alghifari Fajeri (Universitas Lambung Mangkurat, 2023)
AbstractThe Structure and Meaning of The Dayak Ngaju Traditional Marriage Processes. The lack of written works related to the culture of the Dayak Ngaju tribe is the most basic thing so this research is very important to be explored as an effort to document local cultural forms. The research aims to explore the culture of the Dayak Ngaju tribe so it will be known and understood in terms of the meaning contained in the traditional wedding procession. The research result can be used as a foundation for conducting the traditional wedding. The research approach is qualitative with an explorative method and descriptive method. The research data are in the form of Dayak Ngaju people’s activities related to the procession and items of customary requirements. The data sources include traditional leaders, mantir (assistant of traditional apparatus), and public figures. The data collection techniques employ observation techniques, recording, and interviews. The research results indicate that the structure of Dayak Ngaju traditional wedding starts with the fulfillment of “jalan hadat” by conducting “amak rakang injang” by meeting the 20 requirements paid by the groom and it is ended with the fulfillment of the final condition called “batu kaja” that is paid during the “pakaja manantu” (the procession of taking the bride to the groom family after the wedding procession). The meaning of the traditional wedding procession is teaching the procedures of “belum bahadat” (civilized life) so that humans have respect, good manners, and morals.Keywords: Structure, meaning, traditional mating, Ngaju DayakAbstrak Struktur dan Makna Prosesi Perkawinan Adat Dayak Ngaju. Minimnya karya tulis terkait kebudayaan suku Dayak Ngaju menjadi hal yang paling mendasar sehingga penelitian ini sangat penting untuk digali sebagai upaya pendokumentasian bentuk kebudayaan lokal. Tujuan penelitian untuk mengeksplorasikan kebudayaan suku Dayak Ngaju agar tidak hanya dikenal tetapi dapat dipahami pula makna yang terkandung dalam prosesi perkawinan adat tersebut. Hasil penelitian ini dapat dijadikan sebagai pijakan jika ingin melangsungkan pernikahan melalui adat. Pendekatan dalam penelitian ini menggunakan kualitatif dengan metode eksploratif dan deskriptif. Data dalam penelitian ini adalah wujud aktivitas masyarakat Dayak Ngaju terkait prosesi perkawinan adat serta benda-benda yang menjadi syarat adat, sedangkan sumber data adalah ketua adat, mantir, dan tokoh masyarakat. Adapun teknik pengumpulan data, yaitu observasi, rekaman, dan wawancara. Dari hasil penelitian tentang struktur dalam kawin adat suku Dayak Ngaju dimulai dari pemenuhan jalan hadat dengan menggelar amak rakang injang sebagai tanda dimulainya pemenuhan jalan adat perkawinan suku Dayak Ngaju dengan memenuhi 20 syarat yang dibayarkan mempelai laki-laki dan ditutup dengan pemenuhan syarat terakhir yang disebut batu kaja yang dibayarkan saat prosesi pakaja manantu (ngunduh mantu). Adapun makna yang terkandung dalam prosesi kawin adat pada dasarnya mengajarkan tata cara ‘belum bahadat’ (hidup beradab) agar manusia memiliki sikap hormat, berbudi pekerti, dan bermoral.Kata kunci: struktur, makna, kawin adat, Dayak Ngaju